2022
DOI: 10.1111/phor.12419
|View full text |Cite
|
Sign up to set email alerts
|

Digital Elevation Model‐Assisted Aerial Triangulation Method On An Unmanned Aerial Vehicle Sweeping Camera System

Abstract: The sweeping camera systems in the surveying and mapping industry are usually efficient in image acquisition, for the photography coverage of a single strip is relatively large. The triangulation angle of correspondence is overly tiny to adopt traditional block adjustment (BA). This study analysed the imaging principle of the Chinese APS7K comprehensive camera system and proposed an aerial triangulation method for the data this system acquired. The proposed method first determines the adjacent matrix from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For each feature f detected in L1, search for its conjugate point f in R1 using the gray template matching method. To avoid matching outliers and save computation time, use the elements of exterior orientation and average ground elevation to predict the position of its conjugate point and limit the initial search range 39 . In template matching, the NCC is used to calculate the similarity of two pixels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each feature f detected in L1, search for its conjugate point f in R1 using the gray template matching method. To avoid matching outliers and save computation time, use the elements of exterior orientation and average ground elevation to predict the position of its conjugate point and limit the initial search range 39 . In template matching, the NCC is used to calculate the similarity of two pixels.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid matching outliers and save computation time, use the elements of exterior orientation and average ground elevation to predict the position of its conjugate point and limit the initial search range. 39 In template matching, the NCC is used to calculate the similarity of two pixels. According to the winner-take-all scheme, 40 the point with the highest similarity is regarded as the matching point.…”
Section: Generation Of Reference Disparity Mapmentioning
confidence: 99%
“…In order to solve this problem, the existing control source, such as DEM, is considered to be added to the BBA properly. The DEM is directly used as an elevational reference [44]- [46]. Cheng et al [47] took the elevation value extracted from the DEM as the observed value with errors, and then build BBA model combined with the measured image coordinates.…”
Section: B Bba Of Weak-convergence Imagesmentioning
confidence: 99%
“…A3 Edge is the next generation of A3. ABWI also has an old generation, but it's loaded on the UAV (Zhao et al, 2022).…”
Section: Sensor Parametersmentioning
confidence: 99%